Current Trends in the Development of Drugs for the Treatment of Alzheimer’s Disease and their Clinical Trials - Bachurin, S.O.; Bovina, E.V.; Ustyugov, A.A. (Biomedical Chemistry: Research and Methods, 2018)
Intracellular and extracellular accumulation of fibrillary proteins, beta-amyloid and hyperphosphorylated Tau, in patients with Alzheimer’s disease (AD) leads to chronic and progressive neurodegenerative process. Overaccumulation of aggregates results in synaptic dysfunction and inevitable neuronal loss. Although the exact molecular pathways of the AD still require better understanding, it is clear this neuropathology is a multifactorial disorder where the advanced age is the main risk factor. Lately, several dozens of drug candidates have succeeded to phase II clinical trials; however, none has passed phase III. In this review we summarize existing data on anti-AD therapeutic agents currently undergoing clinical trials and included in the public websites www.clinicaltrials.gov and Alzforum.org as well as the Thomson Reuters «Integrity» database. We revealed three major trends in AD drug discovery. First, developing of “disease-modifying agents” could potentially slow the progression of structural and functional abnormalities in the central nervous system providing sustainable improvements of cognitive functions, which persist even after drug withdrawal. Secondly, the focused design of multitargeted drugs acting on multiple key molecular pathways. Finally, the repositioning of drugs that are already available on the market for the novel (anti-AD) application provides a promising strategy for finishing clinical trials and re-marketing.